Scientific production on open science in Information Science: a study based on the ENANCIB event - de Araújo Telmo, Flávia; Matos Autran, Marynice de Medeiros; Araújo da Silva, Alzira Karla (AWARI, 2021)
Open Science has been consolidated as a strategy for building and accessing the knowledge produced in the scientific community. This study analyzes the scientific production on Open Science presented at the National Meeting of Research in Information Science (ENANCIB, in Portuguese). The analysis was based on critical-reflexive inference about the recovered materials, using social network analysis to analyze co-authorship networks. We identified 93 papers during 2015-2019, evidencing an increasing evolution. The papers mainly were presented as oral communication/full papers and expanded posters/abstracts. The Political and Information Economy Working Groups (GT5), Information Production and Communication in Science, Technology & Innovation (GT7), and Information and Technology (GT8) stood out in the topic output. The co-authorship networks displayed 180 actors oriented to open data, open government data, open innovation, academic social networks, data reuse and research data sharing. We also visualized a focus on topics dealing with scientific communication, the law on access to information, open science, access to information, open data, open access, information science, transparency, open government data, public information, public transparency, research data, among others. We concluded that Information Science makes substantial contributions to discussions on Open Science.